The Lack of Researchers: A Critical Threat to Studies on Freshwater Zooplankton in Latin America - Carlos López; Claudia Bonecker; Gilmar Perbiche-Neves; Manuel Elías-Gutiérrez (Diversity, 2025)
We highlight the lack of researchers studying freshwater zooplankton in Latin America and contextualize it within the global extinction of taxonomists, global loss of biodiversity, and regional reality to visualize the intensity of this threat and possible strategies for addressing it. The scarcity of researchers working on freshwater zooplankton currently threatens the future of these studies in the world. This global trend of the decreasing interest of scientists and local governments in learning about this important component of freshwater biodiversity is more accentuated in Latin America by regional drivers, such as brain drain, a lack of support by stakeholders, and the absence of planning for the rational use and conservation of this essential natural resource. All these drivers interact and have more dramatic consequences for regional research due to the recent reduction in government funds for science in some of these countries. In the context of Global Change; a loss of biodiversity due to this fact; and the misuse of drainage basins, overexploitation, and regional pressures, the lack of researchers studying freshwater zooplankton and, in general, all aquatic life has emerged as a critical threat to the delicate equilibrium of these ecosystems. Within this situation, scientific integration through intra-regional and extra-regional collaboration networks has emerged as an unavoidable strategy for the survival and future strengthening of studies on biodiversity and the conservation of freshwater zooplankton in Latin America. The development of new technologies such as DNA barcoding, metabarcoding, and metagenomics has emerged as a solution to this problem. Nevertheless, they should be considered as new tools towards integrative taxonomy and not as replacements for taxonomical studies.